Balanced Growth Despite Uzawa - Gene Grossman; Elhanan Helpman; Ezra Oberfield; Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2016)
Evidence for the United States suggests balanced growth despite falling investment-good prices and less than unitary elasticity of substitution between capital and labor. This is inconsistent with the Uzawa Growth Theorem. We extend Uzawa.s theorem to show that introducing human capital accumulation in the standard way does not resolve the puzzle. However, balanced growth is possible if education is endogenous and capital is more complementary with schooling than with raw labor. We describe balanced growth paths for several neoclassical growth models with capital-augmenting technological progress and endogenous schooling. The balanced growth path in an overlapping-generations model in which individuals choose their time in school matches key features of the U.S. record.
Keywords: O41; 330; neoclassical growth; balanced growth; technological progress; capital-skill complementarity